Managerial sensemaking in public policy implementation: A qualitative study of decisionmaking in local government organizations - Andi Agung Adiguna Al Arifin; Sewang Sewang; Suprianto K; Hery Fadly (Institute of Computer Science (IOCS), 2026)
Public policy implementation in local government organizations is frequently characterized by ambiguity, competing interpretations, and institutional constraints that shape managerial decisionmaking. While prior studies on policy implementation have largely emphasized structural, regulatory, and procedural factors, limited attention has been given to the interpretive processes through which managers make sense of policy directives in practice. This study examines managerial sensemaking in the implementation of public policies within local government organizations, focusing on how managers interpret, negotiate, and translate policy mandates into concrete decisions and actions. Employing an interpretive qualitative approach, this research adopts a case study design involving indepth semistructured interviews with key managerial actors across multiple organizational levels, complemented by document analysis of relevant policy texts. The findings reveal that managerial decisionmaking is not merely a function of formal rules but emerges from ongoing sensemaking processes shaped by prior experience, organizational norms, power relations, and perceived implementation risks. Managers actively construct meanings to reduce uncertainty, reconcile policy ambiguities, and align institutional expectations with operational realities. This study contributes to public management and organizational theory by extending sensemaking perspectives into the context of local government policy implementation. Practically, the findings offer insights for policymakers and public managers to design policies that are more interpretable and actionable, thereby enhancing implementation effectiveness in decentralized governance settings.